2017
DOI: 10.1186/s12911-017-0569-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nursing participation in the design of a critical care information system: a case study in a Chinese hospital

Abstract: BackgroundIntensive care information systems (ICIS) are continuously evolving to meet the ever changing information needs of intensive care units (ICUs), providing the backbone for a safe, intelligent and efficient patient care environment. Although beneficial for the international advancement in building smart environments to transform ICU services, knowledge about the contemporary development of ICIS worldwide, their usage and impacts is limited. This study aimed to fill this knowledge gap by researching the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 35 publications
0
28
0
3
Order By: Relevance
“…This requires the implementation of effective and optimized querying systems (T22) [33] in order to reduce the computational complexity of handling these data. In addition, evaluation of health information system (T31) focuses on the quality management and evaluation of the system,such as those on the effect on health services [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…This requires the implementation of effective and optimized querying systems (T22) [33] in order to reduce the computational complexity of handling these data. In addition, evaluation of health information system (T31) focuses on the quality management and evaluation of the system,such as those on the effect on health services [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also showed that the amount of time spent by nurses in each of the nursing activities differed among different ICU departments; nevertheless, a general assessment showed that from the highest to lowest, the order for timeconsumption of the six types of nursing activities is as follows: direct nursing care > nursing documentation > communication > indirect nursing care > personal affairs > miscellaneous affairs. Regarding nursing documentation time-consumption, when compared to manual documentation, the application of an intensive care information system was shown to significantly shorten the time spent by nurses on documentation procedures from 3.8 to 2.05 hr in a 12-hr period (Qin et al, 2017). However, in our study, registered nurses still had to spend a great deal of time on documentation, especially during the night shift, which is consistent with those of a Brazilian study on ICUs (Kakushi & Evora, 2014).…”
Section: 71%]mentioning
confidence: 99%
“…As not all pregnant women with clinically confirmed COVID-19 presented with fever or other clinical symptoms, it was essential to maintain a high degree of vigilance and follow strict hygiene, disinfection, and isolation protocols when caring for the women ( Moore and Rendall, 2014 , Qin et al., 2017 ). All the procedures described in this paper are based on best practice.…”
Section: Midwifery and Nursing Measures And Recommendationsmentioning
confidence: 99%